Performance Characterisation of the Airvo2TM Nebuliser Adapter in Combination with the Aerogen SoloTM Vibrating Mesh Nebuliser for in Line Aerosol Therapy during High Flow Nasal Oxygen Therapy - Ronan MacLoughlin; Marc Mac Giolla Eain (MDPI AG, 2024)
High flow oxygen (HFO) therapy is a well-established treatment in respiratory disease. Concurrent aerosol delivery can greatly expediate their recovery. The aim of this work was to complete a comprehensive characterisation of one such HFO therapy system, the Airvo2TM, used in combination with the Aerogen SoloTM vibrating mesh nebuliser. Representative adult, infant, and paediatric head models were connected to a breathing simulator via a collection filter placed at the level of the trachea. A tracheostomy interface and nasal cannulas were used to deliver the aerosol. Cannula size and gas flow rate were varied across the full operating range recommended by the manufacturer. The tracheal and emitted doses were quantified via UV-spectrophotometry. The aerosol droplet diameter at the exit of the nares and tracheal interface was measured via cascade impaction. High gas flow rates resulted in low emitted and tracheal doses (%). Nasal cannula size had no significant effect on the tracheal dose (%) available in infant and paediatric models. Higher gas flow rates resulted in smaller aerosol droplets at the exit of the nares and tracheostomy interface. Gas flow rate was found to be the primary parameter affecting aerosol delivery. Thus, gas flow rates should be kept low and where possible, delivered using larger nasal cannulas to maximise aerosol delivery.